Diagnostic and prognostic predictive values of triggering receptor expressed on myeloid cell-1 expression in neonatal sepsis: A meta-analysis and systematic review - Chang, Chenyang; Gao, Qiannan; Deng, Guoping; Luo, Kaiyuan; Zhu, Huifang (Frontiers in Pediatrics, 2022)
Abstract Objective: The purpose of this systematic review was to explore the value of triggering receptor expressed on myeloid cell-1 (TREM-1) expression level in the diagnosis and prognosis of neonatal sepsis. Methods: A comprehensive search was performed to identify the diagnostic and prognostic predictive values of TREM-1 expression level in neonatal sepsis. Based on the retrieval strategy, Cochrane Library, Embase, Ovid, ProQuest, PubMed, Scopus and Web of Science databases were searched from inception to February 2022. Studies were included if they assessed accuracy of TREM-1 expression in the diagnosis of neonatal sepsis and distinguishing survival and death in neonatal sepsis. Two authors independently evaluated the study and extracted the data, consulting a third party if disputed. The accuracy of TREM-1 expression in the diagnosis and prognostic prediction of neonatal sepsis was evaluated by a bivariate mixed effects model. The source of heterogeneity was explored through meta-regression analysis. Results: A total of 13 articles, involved 987 newborns were included in the qualitative analysis. The pooled sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), diagnostic odds ratio (DOR) and the area under the summary receiver operator characteristic (SROC) curve of TREM-1 were 0.94 (95% CI: 0.82, 0.98), 0.87 (95% CI: 0.70, 0.95), 7.36 (95% CI: 2.75, 19.74), 0.07 (95% CI: 0.02, 0.24), 111.71 (95% CI: 13.24, 942.92) and 0.96 (95% CI: 0.94, 0.98), respectively. Meta-regression analysis and subgroup analysis was used to investigate the heterogeneity, owing to non-threshold effects caused by types of test sample and research design. TREM-1 expression as a biomarker for distinguishing survival and death in neonates with sepsis had pooled sensitivity, specificity, area under the SROC curve, PLR, NLR and DOR of 0.95 (95% CI: 0.83, 0.99), 0.98 (95% CI: 0.68, 1.00), 0.99 (95% CI: 0.97, 0.99), 39.28 (95% CI: 2.13, 723.99), 0.05 (95% CI: 0.01, 0.19) and 789.61 (95% CI: 17.53, 35560.72), respectively. Conclusions: The study showed that TREM-1 was a potential biomarker for the diagnosis and prognosis of neonatal sepsis. Keywords: TREM-1, sTREM-1, neonatal sepsis, diagnosis, prognosis